Perancangan Desain Antarmuka Website Katalog Produk Furniture (Studi Kasus: UD. Prana Meubel) - Kurniawan, Bagas; Karnadi, Karnadi (CV. Multi Kreasi Media, 2024)
This study aims to design an optimal furniture product catalog website interface design with a focus on aspects of functionality, clarity, aesthetics, and responsiveness, using UD. Prana Meubel as a case study. Through analysis of the company's business needs, understanding of user preferences, and exploration of effective design trends, this research resulted in an interface design that reflects UD's brand identity. Prana Meubel, pays attention to product search functionality, intuitive navigation, as well as attractive product visualization. It is hoped that the results of this study can contribute to the understanding of the importance of website interface design in the furniture industry, as well as provide practical guidance for similar companies in improving their online presence and user experience.